Soybean Isoflavones Eliminate Nifedipine-Induced Flushing of Tail Skin in Ovariectomized Mice - Mamiko Kai; Atsushi Yamauchi; Koji Tominaga; Ayako Koga; Hisashi Kai; Yasufumi Kataoka (Elsevier, 2004)
Hot flushes are one of the most frequent symptoms in menopausal women. We investigated effect of soybean isoflavones (Soyaflavone HG) on nifedipine-induced flushing in ovariectomized mice. Ovariectomy markedly aggravated nifedipine-induced increase in tail skin temperature. Soyaflavone HG (10 mg/kg, p.o., once a day for 5 days) inhibited nifedipine-induced flushing in ovariectomized mice. The inhibitory effect of Soyaflavone HG was significantly reversed by an estrogen-receptor antagonist, ICI 182,780, suggesting that Soyaflavone HG prevents nifedipine-induced flushing partially through estrogen receptors. We presented the experimental evidence suggesting that soybean isoflavones including Soyaflavone HG have the benefits for menopausal hot flushes. Keywords:: soybean isoflavone, menopausal flushing, ovariectomy